Production Of Poly(3-Hydroxybutyrate-Co-3-Hydroxyvalerate) By Cupriavidus Malaysiensis Usmaa2-4Abh16 Harbouring Cupriavidus Necator H16 Lipase Gene - Jeremy, Wong Hau Seung (2023)
Polyhydroxyalkanoates (PHA) are biopolyesters with thermoplastic properties that are biocompatible and biodegradable. Poly(3-hydroxybutyrate) [P(3HB)] is the most common PHA produced by various microorganisms, but its application is limited due to its stiffness. Incorporating a secondary monomer such as 3-hydroxyvalerate (3HV) contributes to several PHA properties improvement, including flexibility, elasticity, and biodegradability. High-cost oleic acid and organic acids are preferred by most PHA-producing bacteria as the carbon sources for poly(3-hydroxybutyrate-co-3-hydroxyvalerate) [P(3HB-co-3HV)] production. This study demonstrated the evaluation of a lipase genes-harbouring transformant for PHA production from palm olein and 1-pentanol as alternatives to oleic acid and valeric acid. In this study, a clone, Cupriavidus malaysiensis USMAA2-4ABH16 which is the transformant of C. malaysiensis USMAA2-4 was successfully constructed. C. malaysiensis USMAA2-4ABH16 harbouring expressible Cupriavidus necator H16 lipAB genes accumulated more than 60 wt% of P(3HB-co-3HV) using palm olein and 1-pentanol as the carbon sources. Nucleotide sequence alignment of the lipAB insert showed 100% identities with C. necator H16 lipAB genes and expect value of 0.0. C. malaysiensis USMAA2-4ABH16 showed 4-fold higher growth and 8-fold higher lipase activity compared to C. necator H16 under cobalt and alcohol stress.